Key constituents for integration of care for children assisted with long-term home ventilation: a European study - Maria Brenner; Miriam P. O'Shea; Philip Larkin; Jay Berry (BMC, 2020)
Abstract Background The number of children requiring long-term home ventilation has consistently increased over the last 25 years. Given the growing population of children with complex care needs (CCNs), this was an important area of focus within the Models of Child Health Appraised (MOCHA) project, funded by the European Union (EU) under the Horizon 2020 programme. We examined the structures and processes of care in place for children with CCNs and identified key constituents for effective integration of care for these children at the community and acute care interface across 30 EU/ European Economic Area (EEA) countries. Methods This was a non-experimental descriptive study with an embedded qualitative element. Data were collected by a Country Agent in each of the 30 countries, a local expert in child health services. Data were analysed using descriptive statistics and a thematic analysis was undertaken of the free text data provided. Results A total of 27 surveys were returned from a possible 30 countries (90.0%) countries. One respondent indicated that their country does not have children on long-term ventilation (LTV) in the home, therefore, responses of 26 countries (86.7%) were analysed. None of the responding countries reported that they had all of the core components in place in their country. Three themes emerged from the free text provided: 'family preparedness for transitioning to home', 'coordinated pathway to specialist care' and 'legal and governance structures'. Conclusions While the clinical care of children on LTV in the acute sector has received considerable attention, the results identify the need for an enhanced focus on the care required following discharge to the community setting. The results highlight the need for a commitment to supporting care delivery that acknowledges the complexity of contemporary child health issues and the context of the families that become their primary care givers.